2005
DOI: 10.4103/0972-9941.16527
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy relevant to cholecystectomy

Abstract: This review discusses anatomical facts that are of relevance to the performance of a safe cholecystectomy. Misinterpretation of normal anatomy and anatomical variations contribute to the occurrence of major postoperative complications like biliary injuries following a cholecystectomy, the incidence being higher with laparoscopic cholecystectomy. A look at the basic anatomy is therefore important for biliary and minimally invasive surgeons. This includes normal anatomy and variations of the biliary apparatus as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 7 publications
2
78
0
3
Order By: Relevance
“…The most important patientrelated risk factors of operative bleeding are acute cholecystitis, liver cirrhosis, previous abdominal surgery, peritoneal adhesion and anatomical abnormalities [18][19][20]. Our data came in agreement with these results as we observed that operative bleeding was 7.84% in patients with acute cholecystitis, fibrotic gall bladder and extensive peritoneal adhesion.…”
Section: Discussionsupporting
confidence: 90%
“…The most important patientrelated risk factors of operative bleeding are acute cholecystitis, liver cirrhosis, previous abdominal surgery, peritoneal adhesion and anatomical abnormalities [18][19][20]. Our data came in agreement with these results as we observed that operative bleeding was 7.84% in patients with acute cholecystitis, fibrotic gall bladder and extensive peritoneal adhesion.…”
Section: Discussionsupporting
confidence: 90%
“…Anatomical landmarks in calot's triangle now could be easily identified paving the way to safe cholecystectomy. 11,12 If untreated, the wall echo complex is likely to form cholecystoduodenal fistula particularly if the calculi are present in the neck of gall bladder. This wall echo complex leads to inflammation, adhesion and erosion of duodenum.…”
Section: Discussionmentioning
confidence: 99%
“…Jonson et al (6) stated that several reports have proposed that a cystic duct remnant >1 cm in length after cholecystectomy may be responsible, at least in part, for postcholecystectomy syndrome. Nagral (7) reported that anatomical facts are of relevance to the performance of a safe cholecystectomy. Misinterpretation of normal anatomy and anatomical variations contribute to the occurrence of major postoperative complications like biliary injuries following a cholecystectomy, the incidence being higher with laparoscopic cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%